Socio-economic Development of Russia - NAZAROVA, Lionella Nikolaevna; NUSRATULLIN, Ilmir Vilovich; AKSENOVA, Anastasiya Andreyevna; GAZIZYANOVA, Yuliya Yunusovna; TIKHONOV, Aleksey Ivanovich (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The purpose of this study is to analyze the functioning of socio-economic development mechanism on the example of the Russian Federation, to provide conceptual justification of measures to improve the interactive response to the sustainable development of the territory using a cluster approach in the economic context. The study was implemented using a set of methods: including principles allowing for the use of general scientific and economic methods, which are a synthesis of abstract-theoretical analysis, system, factor, and structural-functional analysis, logical approach, statistical methods, simulation, situational and quantitative approaches. The author also applied private methodological tools of economic and mathematical modeling and others. The study substantiates measures to improve the regional mechanism of socio-economic development in a specific socio-economic space of the Russian Federation, which allows initiating the emergence of a significant multiplier effect in managing the economics of state development. Theoretical conclusions and suggestions can be used for further scientific development of the problem of regional socio-economic policy and allow an economic interpretation of the problems of sustainable socio-economic development of the territory. The results of the analysis and the identified trends presented in this study work are of independent value since they can serve as a basis for improving the efficiency of economists’ management decisions and developing the state socio-economic system when developing strategic guidelines for the socio-economic policy of sustainable development of the Russian Federation.